Assessment of the Prognostic Value of Two Common Variants of BRCA1 and BRCA2 Genes in Ovarian Cancer Patients Treated with Cisplatin and Paclitaxel: A Gynecologic Oncology Group Study - Tian, Chunqiao; Darcy, Kathleen M.; Ambrosone, Christine B.; Krivak, Thomas C. (Frontiers in Oncology, 2013)
Purpose: BRCA1/BRCA2 germline mutations appear to enhance the platinum-sensitivity, but little is known about the prognostic relevance of polymorphisms in BRCA1/BRCA2 in epithelial ovarian cancer (EOC). This study evaluated whether common variants of BRCA1/BRCA2 are associated with progression-free survival (PFS) and overall survival (OS) in patients with advanced stage sporadic EOC. Experimental Design: The allelic frequency of BRCA1 (2612C>T, P871L-rs799917) and BRCA2 (114A>C, N372H-rs144848) were determined in normal blood DNA from women in Gynecologic Oncology Group (GOG) protocol #172 phase III trial with optimally-resected stage III EOC treated with intraperitoneal or intravenous cisplatin and paclitaxel (C+P). Associations between polymorphisms and PFS or OS were assessed. Results: 232 women were included for analyses. African Americans (AA) had different distributions for the two polymorphisms from Caucasians and others. For non-AA patients, the genotype for BRCA1 P871L was distributed as 38% for CC, 49% for CT and 13% for TT. Median PFS was estimated to be 31, 21 and 21 months, respectively. After adjusting for cell type, residual disease and chemotherapy regimen, CT/TT genotypes were associated with a 1.40-fold increased risk of disease progression (95% confidence interval [CI]=1.00-1.95, p=0.049). After removing 7 patients with known BRCA1 germline mutations, the hazard ratio (HR) was 1.36 (95% CI=0.97-1.91, p=0.073). The association between BRCA1 P871L and OS was not significant (HR =1.25, 95% CI=0.88-1.76, p=0.212). Genotype distribution of BRCA2 N372H among non-AA patients was 50%, 44% and 6% for AA, AC and CC, respectively and there is no evidence that this BRCA2 polymorphism was related to PFS or OS. Conclusion: Polymorphisms in BRCA1 P871L or in BRCA2 N372H were not associated with either PFS or OS in women with optimally-resected, stage III EOC treated with cisplatin and paclitaxel.